Synthesis of Quinoline and Quinolin-2(1H)-one Derivatives via Nickel Boride Promoted Reductive Cyclization - Sarkar, Rumpa; Samanta, Surya Kanta; Menon, Anila M.; Chopra, Deepak; Ganguly, Debabani; Bera, Mrinal K. (Synthesis, 2023)
A mild and efficient approach for the synthesis of diversely substituted quinoline and quinolin-2-one derivatives is disclosed. In situ generated nickel boride proved to be an effective promoter of the reductive cyclization reaction. Broad substrate scope, mild reaction conditions, consistent yield, and a wide range of functional group tolerance are the other notable features of the newly discovered reaction. A large number of quinoline and quinolin-2-one derivatives may be prepared from milligram to multigram scale employing this intramolecular reductive cyclization protocol.
Keywords: quinolines; quinolin-2(1H)-ones; nickel boride; sodium borohydride; reductive cyclization